Product Development of Natural Fibre-Composites for Various Applications: Design for Sustainability - Asyraf M.R.M.; Syamsir A.; Zahari N.M.; Supian A.B.M.; Ishak M.R.; Sapuan S.M.; Sharma S.; Rashedi A.; Razman M.R.; Zakaria S.Z.S.; Ilyas R.A.; Rashid M.Z.A. (MDPI, 2023)
Concurrent engineering; Ecodesign; Fiber reinforced plastics; Natural fibers; Product design; Product development; Sustainable development; 'current; Application design; Concept designs; Concept embodiments; Design-process; Detail design; Embodiment design; Natural fiber composites; New product development; Sustainability development; Conceptual design